Dynamics and aerodynamics of deciduous urban trees - Roodbaraky, Hilary Jane (1994)
Strong winds cause a great deal of damage to trees, and these falling trees inevitably damage property, communication lines and may even cause fatalities. This thesis presents an investigation into tree stability.